2014
DOI: 10.1152/ajpendo.00428.2013
|View full text |Cite
|
Sign up to set email alerts
|

Increased myocardial ischemia-reperfusion injury in renal failure involves cardiac adiponectin signal deficiency

Abstract: Tao L. Increased myocardial ischemiareperfusion injury in renal failure involves cardiac adiponectin signal deficiency. Am J Physiol Endocrinol Metab 306: E1055-E1064, 2014. First published March 4, 2014 doi:10.1152/ajpendo.00428.2013.-Plasma levels of adiponectin (APN) are significantly increased in patients with renal dysfunction and are inversely related to the risk of cardiovascular mortality. The present study was designed to determine the role of APN in myocardial ischemia-reperfusion (MI/R) injury in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…Thus, although a rat with 5/6 nephrectomy is an established model of CKD [3,8,12,35], impaired Aktmediated signaling upon reperfusion shown by the present study is unlikely to be the only mechanism of increased myocardial susceptibility to ischemia/reperfusion in CKD. In fact, mitochondrial dysfunction [36] and down-regulated expression of the adiponectin receptor in the myocardium [35] were reported to be associated with increased myocardial injury by CKD. In our study conducted in parallel with this study [26], disturbed malate-aspartate shuttle in the myocardium in CKD was indicated by results of metabolome analysis.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, although a rat with 5/6 nephrectomy is an established model of CKD [3,8,12,35], impaired Aktmediated signaling upon reperfusion shown by the present study is unlikely to be the only mechanism of increased myocardial susceptibility to ischemia/reperfusion in CKD. In fact, mitochondrial dysfunction [36] and down-regulated expression of the adiponectin receptor in the myocardium [35] were reported to be associated with increased myocardial injury by CKD. In our study conducted in parallel with this study [26], disturbed malate-aspartate shuttle in the myocardium in CKD was indicated by results of metabolome analysis.…”
Section: Discussionmentioning
confidence: 65%
“…At least during the first week, graft dysfunction did not reflect impaired clearance of ADPN, suggesting that factors other than renal function may be involved. A study from Song and coworkers [34] demonstrated a decline in circulating ADPN levels during the initial 72 h after a subtotal nephrectomy in mice with renal failure, associated to down regulation of ADPN. Following this reasoning, we can also speculate that the decrease of circulating ADPN levels observed within the first week after KTx could be due to two different mechanisms according to graft function: enhanced filtration of circulating ADPN and urinary excretion in prompt graft patients; and decline in local expression of ADPN in glomerular endothelium as a result of amplified ischemia-reperfusion injury that usually describes DGF.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of stress stimuli generate excessive ceramide through sphingolipid metabolism. As a secondary signaling molecule, it activates the signal transduction required for the occurrence of biological processes such as in ammation, apoptosis, and cellular differentiation [21,22]. Accumulating evidence has validated that the ceramide accumulation triggers the assembly and activation of NLRP3 in ammasome in various pathological conditions [7,8].…”
Section: Discussionmentioning
confidence: 99%